Contemporary issues in Islam: for undergraduate students - Ali, Mohammed Farid (2017)
This book consists of three parts: Part One is on contemporary challenges faced by Muslims and humanity, Part two on the future of the ummah: Challenges and prospects and part three on contemporary applications of ethics and fiqh. This PROJECT will employ a qualitative approach using a six-tier technique: a. Library research to collect data on the latest literature on the existing contemporary issues discussed in the three core-courses; b. Library research to collect data on the new contemporary issues; c. Analysis of the data to find substance suitable for the text book; d. Writing of chapters and submission of first draft; f. Standardizing the pedagogical style; g. Finalizing the drafts and submission.